Convenient method for preparation of aryl sulfinates from arenes and DABSO as the SO2 surrogates. Issue 13 (28th March 2018) - Wang, Tianlei; Wang, Fumin; Shen, Jinghua; Pang, Tianting; Ren, Yanfei; Wu, Botao; Zhang, Xubin
Graphical abstract: Highlights: Simple preparation method, mild conditions and cheap reactants for the synthesis of aryl sulfinates. In situ infrared spectroscopic studies for this sulfination reaction and a plausible mechanism is proposed. Solid, stable SO2 surrogates are used instead of toxic gas SO2 . Abstract: A safe and efficient protocol for the synthesis of aryl sulfinates from arenes and 1, 4-diazabicyclo[2, 2, 2]octane bis(sulfur dioxide) (DABSO) under mild conditions is described. Through in situ infrared spectroscopic studies, a plausible mechanism for the sulfination reaction is proposed as well.